#### Answer

$z=-13$

#### Work Step by Step

$z^2+26z+169=0$
$z^2+13z+13z+13*13=0$
$z(z+13)+13(z+13)=0$
$(z+13)(z+13)=0$
$z+13=0$
$z=-13$

Published by
Prentice Hall

ISBN 10:
0133281140

ISBN 13:
978-0-13328-114-9

$z=-13$

$z^2+26z+169=0$
$z^2+13z+13z+13*13=0$
$z(z+13)+13(z+13)=0$
$(z+13)(z+13)=0$
$z+13=0$
$z=-13$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.